Arg-Vasotocin Directly Activates Isotocin Receptors and Induces COX2 Expression in Ovoviviparous Guppies - Lyu, Li Kang; Li, Jian Shuang; Wang, Xiao Jie; Yao, Yi Jia; Li, Ji Fang; Li, Yun; Wen, Hai Shen; Qi, Xin (Frontiers in Endocrinology, 2021)
Oxytocin (OT) is a crucial regulator of reproductive behaviours, including parturition in mammals. Arg-vasopressin (APV) is a nonapeptide homologous to Arg-vasotocin (AVT) in teleosts that has comparable affinity for the OT receptor. In the present study, ovoviviparous guppies (Poecilia reticulata) were used to study the effect of AVT on delivery mediated by the activation of prostaglandin (PG) biosynthesis via isotocin (IT) receptors (ITRs). One copy each of it and avt and two copies of itrs were identified in guppies. The results of the affinity assay showed that various concentrations of AVT and IT (10-6 mol/L, 10-7 mol/L and 10-8 mol/L) significantly activated itr1 (P < 0.05). In vitro experiments revealed significant upregulation (P < 0.05) of cyclooxygenase 2 (cox2), which is the rate-limiting enzyme involved in PG biosynthesis, and itr1 by AVT and IT. Furthermore, dual in situ hybridization detected positive signals for itr1 and cox2 at the same site, implying that ITR1 may regulate cox2 gene expression. Measurement of prostaglandin F2a (PGF2a) concentrations showed that AVT induced PGF2a synthesis (P < 0.05) and that the effect of IT was not significant. Finally, intraperitoneal administration of PGF2a significantly induced premature parturition of guppies. This study is the first to identify and characterize AVT and ITRs in guppies. The findings suggest that AVT promotes PG biosynthesis via ITR and that PGF2a induces delivery behaviour in ovoviviparous guppies.